Uncovering collateral damages and advanced defense strategies in cloud environments against DDoS attacks: A comprehensive review - Verma, Priyanka; Bharot, Nitesh; Breslin, John G.; Sharma, Mukta; Chaurasia, Nisha; Vidyarthi, Ankit (Transactions on emerging telecommunications technologies, 2024)
Cloud computing (CC) offers on‐demand computing and resources to users, and organizations, and is also used in many human‐centric intelligent systems. Attacks in cloud networks cause huge damage to service providers and users. Distributed Denial of Service (DDoS) is one of them that greatly impacts the cloud network. The unavailability of resources is the major concern pertaining to cloud service and resources. Apart from the direct targets of a DDoS attack, there are also indirect effects on non‐targets within a cloud network. These effects on the non‐target stakeholders of the cloud are called collateral damages. However, this area of research is not explored much by researchers. Thus, the defense methods pertaining to direct and indirect effects need to be explored. This article aims to describe the consequences of DDoS attacks and the solutions available in the cloud network. The novelty of this article lies in shedding light on the indirect impacts of DDoS in cloud networks and possible solution approaches. The article also provides a comparative analysis of the existing defense solution under different categories and available tools and datasets to evaluate the proposed solutions. The article also mentions the solution considerations and effective solution scenarios. The idea behind this article is to impart guidelines to the researchers, for developing efficient defense solutions against direct target and indirect target DDoS attacks. Moreover, the research shortcomings, pros–cons, and existing challenges are outlined, and directions for future research are mentioned. This survey examine DDoS attacks in cloud environments, highlighting both direct and indirect consequences. We delve into the collateral damages and discuss existing solutions to mitigate these impacts. The article also offers insights into potential defense strategies for addressing the challenges faced by direct and indirect targets of DDoS attacks.